Dynamics of Dayah Ulama's Thoughts on the Langsa City Qanun Regarding Entertainment Management - Faisal, Faisal; Asmuni, Asmuni; Zainul F, Phil.; Anshori, Ahmad Afnan (Madania: Jurnal Kajian Keislaman, 2024)
The aim of this study is to discuss the dynamics of the understanding of dayah scholars towards Qanun Number 3 of 2016 concerning the Implementation of Entertainment in Langsa City. Qonun was born as a response to public anxiety about the phenomenon of mushrooming entertainment venues and sources of violence among the people of Langsa city. However, what particulary interesting is whether this qanun is accepted by all segments of society, especially by dayah or Acehnese ulama. This study is empirical juridical research. The data collection techniques used in this study were interviews and documentation. Meanwhile, the analysis technique employed is descriptive. This research is conducted in Langsa City, where the Islamization movement is strongly embedded in public spaces and governance. The informants of this research included dayah scholars, chairpersons or members of the Ulema Consultative Assembly (MPU) Langsa city, as well as residents of Langsa city. An important finding of this study is the differing views among dayah scholars on the qanun issued by the Langsa City government, particularly Qanun Number 3 of 2016 regarding the implementation of entertainment in Langsa City. Some scholars approve and support the qanun, while others do not support or see a need for it. The influence of dayah ulama on Qanun Number 3 of 2016 is significant and has support from the people of Langsa city, Consequently, the opinions or fatwas expressed by dayah ulama in the community are considered authoritative and must be followed. Studi ini bertujuan membahas tentang dinamika pemahaman ulama dayah terhadap Qanun Nomor 3 Tahun 2016 Tentang Penyelenggaraan Hiburan di Kota Langsa. Qonun ini lahir sebagai respon dari kegelisahan masyarakat terhadap fenomena menjamurnya tempat tempat hiburan dan sumber kemaksiatan ditengah tengah masyarakat kota Langsa. Namun yang menarik, apakah qonun ini diterima oleh semua kalangan masyarakat terutama oleh para dayah atau ulama Aceh. Studi ini adalah penelitian yuridis empiris. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah teknik wawancara dan dokumentasi. Sedangkan teknik analisa yang digunakan adalah teknik deskriptif analisis. Penelitian ini berlokasi di kota Langsa karena di kota langsa ini gerakan Islamisasi tumbuh kuat dalam ruang publik dan juga dalam tata pemerintahan. Informan penelitian ini berasal dari ulama-ulama dayah, ketua atau anggota Majelis Permusyawaratan Ulama (MPU) kota Langsa, serta warga masyarakat kota Langsa. Temuan penting dalam penelitian ini adalah telah terjadinya perbedaan pandangan ulama dayah terhadap qanun yang dikeluarkan oleh pemerintah kota Langsa khususnya Qanun Nomor 3 Kota Langsa Tahun 2016 tentang penyelenggaraan hiburan di Kota Langsa yaitu ada yang menyetujui dan mendukung, ada yang tidak mendukung dan tidak perlu adanya qanun tersebut. Pengaruh ulama dayah terhadap Qanun Nomor 3 tahun 2016 sangat besar dan mendapat dukungan dari dari masyarakat Kota Langsa sehingga apa yang dikatakan ulama dayah dalam masyarakat merupakan sebuah fatwa atau pendapat yang harus diikuti.